Prevalence of fish lice, Argulus (Crustacea: Branchiura) in freshwater and two ornamental fishes of Iran - Ali Reza Radkhah; Soheil Eagderi (Journal of Fisheries, 2022)
Farming and trading of aquarium fish has been considered a popular pastime in the world. Most of Iran's aquarium fish are imported from Asian countries including Indonesia, Malaysia, Thailand and Vietnam. Fish lice (Argulus) is known as one of the most important and common ectoparasites in ornamental fish. Reports indicate that these parasites have been observed in ornamental fish imported to Iran (e.g goldfish Carassius auratus and koi carp Cyprinus carpio). Today, due to mismanagement of some ornamental fish breeding centres in Iran, aquarium fish species such as goldfish may have escaped into the natural waters which increase the risk of transmitting pathogens to native fish. The present work was performed to investigate the outbreak of an ectoparasite Argulus in two ornamental fish of Iran and also to evaluate the possibility of transmission of Argulus to inland freshwater fishes of Iran.